KEMAMPUAN MENULIS TEKS PUISI BERDASARKAN PENGALAMAN PRIBADI SISWA KELAS VIII SMPS KEMALA BHAYANGKARI 1 KUBU RAYA - Rindawati Rindawati; Martono Martono; Deden Ramdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
ABSTRACTPoetry Writing is one component of the Indonesian Language lessons for grade VIII.The materials require learners to explore ideas and develop their skills andunderstanding. This study focused on exploring the learners’ competence in writingpoetry based on their personal experience. This study aims to describe 1) diction, 2)images, 3) language styles, 4) themes/meaning, and 5) the message of the poetrywritten by students. The method used in this study was descriptive in the form ofquantitative research. The sample of this study was 68 students of class VIII. Thedata collection technique used was a test, and the tool of data collection was testitems. The findings showed that the diction aspect resulted in an excellent categoryby 98.52%, and the image aspect resulted in a fair category by 67.64%. Thelanguage style aspect showed a poor category with a percentage of 48.52%, whereasthe theme aspect showed a good category by 82.35%. The messages aspect showedin a fair category by 60.29%. According to all aspects, the recommendation given tothe teacher is to provide exercises and access to other media to help studentsimprove their writing skills, find broader ideas to write poetry, and enrich thelanguage styles in their poetry writings.Keywords: Poetry writing, Student’s personal experience, Writing skills.